2013
DOI: 10.1016/j.envres.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Family and home characteristics correlate with mold in homes

Abstract: Previously, we demonstrated that infants residing in homes with higher Environmental Relative Moldiness Index were at greater risk for developing asthma by age seven. The purpose of this analysis was to identify the family and home characteristics associated with higher moldiness index values in infants' homes at age one. Univariate linear regression of each characteristic determined that family factors associated with moldiness index were race and income. Home characteristics associated with the moldiness ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 18 publications
2
19
1
1
Order By: Relevance
“…Contrary to other studies (Reponen et al, 2013;Reponen et al, 2011), the origin of the parents and their incomes do not influence the observed microbial composition in homes. We had previously supposed that asthmatic parents would take precautions to reduce the observed microorganism levels in their homes and thus influence the presence or absence of certain fungal species (Reboux et al, 2009).…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Contrary to other studies (Reponen et al, 2013;Reponen et al, 2011), the origin of the parents and their incomes do not influence the observed microbial composition in homes. We had previously supposed that asthmatic parents would take precautions to reduce the observed microorganism levels in their homes and thus influence the presence or absence of certain fungal species (Reboux et al, 2009).…”
Section: Discussioncontrasting
confidence: 83%
“…The 10 targets were simultaneously analyzed and provided essential information about the microbiology of different dwellings. It is for this reason that our study is original with respect to those that target only fungi communities (Reponen et al, 2013;Reponen et al, 2011;Vesper et al, 2007b;Vesper et al, 2007c) or studies which characterized cumulative microorganism exposure (Ege et al, 2011;Karvonen et al, 2014;Roussel et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that sensitization to molds was more likely to co-occur, and frequently cooccurred, with sensitization to dust mites. This is consistent with demonstrated associations between the verified presence of in-home mold and dust (41). Reported exposures were only weakly related to sensitizations-again, consistent with previous work highlighting the disparity between reported and true exposure (21).…”
Section: Original Researchsupporting
confidence: 79%
“…Several variables were confounded, and multivariate analysis suggested that lower overall socioeconomic status was associated with higher ERMI. 85 Similar associations of certain indoor molds with asthma and allergic symptoms (particularly when mold odor was present) were found in single studies and meta-analyses from other Midwestern and worldwide locations. [85][86][87][88][89][90][91][92] Toxic and Irritant Effects: Controversial concerns regarding indoor molds are especially focused around toxic effects.…”
Section: 22mentioning
confidence: 59%